Non-adherence level of pharmacotherapy and its predictors among mental disorders in a resource-limited life trajectories: a systematic review and meta-analysis - Woretaw Sisay Zewdu; Samuel Berihun Dagnew; Getachew Yitayew Tarekegn; Taklo Simeneh Yazie; Meswait Asrat Ayicheh; Fisseha Nigussie Dagnew; Tilaye Arega Moges (BMC Psychiatry)
Abstract Introduction Despite being crucial in ensuring the best treatment outcomes, adherence status is frequently overlooked in comprehensive chronic care. Thus, the present study critically evaluates, integrates, and summarizes psychotropic medication non-adherence and its determinants among patients with mental disorders in a resource limited life trajectories to inform policy and future research. Method Systematic review and meta-analysis following the Cochrane handbook for systematic reviews of interventions and Preferred Reporting Items for Systematic review and Meta-analysis (PRISMA) statement was conducted. PubMed (Medline), CINAHL, PsychINFO, EMBASE, and Google Scholar databases were comprehensively searched to retrieve published and grey literature from index inception to October 2024. Observational original studies focused on the magnitude of psychotropic treatment non-adherence and its predictors were eligible for inclusion. Risk-of-bias was assessed using Joanna Briggs Institute (JBI) criteria. Protocol was pre-registered at PROSPERO with a reference number of CRD42024578766. Results Twenty-three studies (n = 23, 359) were included, 22 of them in the quantitative analysis. The pooled prevalence of non-adherence was 46% (95% CI: 40%-52%, I2 = 96.95%). Subgroup analysis revealed that non-adherence was higher among patients with major depressive disorder (40.43%, I2 = 98.87%). Sociodemographic factors (aOR = 1.58, I2 = 87.13%), patient-related factors (aOR = 1.47, I2 = 25.62%), lack of insight (aOR = 1.24, I2 = 72.12%), negative attitude towards the treatment (aOR = 1.78, I2 = 0.00%), poor social support (aOR = 1.49, I2 = 82.55%), self-stigma (aOR = 1.97, I2 = 30.70%), and drug-related factors (aOR = 1.42, I2 = 64.16%) were the predictors. Substance use was identified as a protective factor for adherence (aOR = 0.84, I2 = 99.97%). Conclusion Altogether, we discovered that psychotropic treatment non-adherence among patients with psychiatric disorders was quite common. This analysis may serve as a high-grade ore for policymakers, though it must be interpreted with caution due to significant heterogeneity. Notwithstanding stringent methodology, depending on cross-sectional studies limits its clinical guidance.